Motivated cognition: effects of reward, emotion, and other motivational factors across a variety of cognitive domains - Madan, Christopher R. (University of California Press, 2017)
A growing body of literature has demonstrated that motivation influences cognitive processing. The breadth of these effects is extensive and span influences of reward, emotion, and other motivational processes across all cognitive domains. As examples, this scope includes studies of emotional memory, value-based attentional capture, emotion effects on semantic processing, reward-related biases in decision making, and the role of approach/avoidance motivation on cognitive scope. Additionally, other less common forms of motivation–cognition interactions, such as self-referential and motoric processing can also be considered instances of motivated cognition. Here I outline some of the evidence indicating the generality and pervasiveness of these motivation influences on cognition, and introduce the associated ‘research nexus’ at Collabra: Psychology.